ANALISIS EKONOMI ISLAM ATAS JUAL BELI (MINDRING) DI DESA SENDAHARJO LAMONGAN - Dheny Adresima, Rima; Latifah, Eny (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2023)
The purpose of this study was to determine the Islamic economic analyze on buying and selling mindring credit models in Sendangharjo Village, Brondong Lamongan. This research uses descriptive qualitative method of case study type. The data analysis technique used is data triangulation by combining data from interviews, observations and documents. The results of this study indicate that the Islamic economic perspective on the mindring model of credit buying and selling consists of five principles, namely monotheism (faith): the fulfillment of the transaction actor, the object of the transaction, and the transaction contract (ijab qabul), 'Adl (justice): the attitude of the seller who does not discriminate -distinguish between one buyer and another, nubuwwah (prophecy): the honesty of the seller in conveying the shortage or excess of goods, khilafah (governance): no restrictions from the village government, and Ma'ad (result): the purpose of mindring service providers running their business those who not only pursue profits but blessings.